A comparative study on laser induced shock cleaning of radioactive contaminants in air and water. (1st March 2018) - Kumar, Aniruddha; Prasad, Manisha; Bhatt, R.B.; Behere, P.G.; Biswas, D.J.
Highlights: UO2 contamination from steel surface was removed using laser generated shock. A nano- second pulsed Nd-YAG laser emitting at 532 nm wavelength was used. Contaminated samples were cleaned in air as well as in water. Best Decontamination Efficiency (DE) was obtained while cleaning in water. DE was dependent on the relative position of the sample wrt the laser beam. Abstract: Efficient removal of Uranium-di-oxide (UO2 ) particulates from stainless steel surface was effected by Nd-YAG laser induced plasma shock waves in air as well as in water environment. The propagation velocity of the generated shock wave was measured by employing the photo-acoustic probe deflection method. Monitoring of the alpha activity of the sample with a ZnS (Ag) scintillation detector before and after the laser exposure allowed the estimation of decontamination efficiency defined as the percentage removal of the initial activity. Experiments were carried out to study the effect of laser pulse energy, number of laser exposures, orientation of the sample, the separation between the substrate surface and the onset point of the shock wave on the de-contamination efficiency. The most optimised cleaning was found to occur when the laser beam impinged normally on the sample that was immersed in water and placed at a distance of ∼0.7 mm from the laser focal spot. Analysis of the cleaned surface by optical microscopes established that laser induced shock cleaning in no way altered the surface property. The shock force generated in both air and water has been estimated theoretically and has been found to exceed the Van der Waal's binding force for spherical contaminant particulate.